Cotton methyl ester usage in a diesel engine equipped with insulated combustion chamber - Hazar, Hanbey (Elsevier Sci Ltd, 2010)
An important alternative for diesel fuel is methyl ester made of vegetable oils. Direct use these fuels without modification in diesel engines causes some damages on the parts of the engines and also, the viscosity of the methyl ester fuels is quite higher than that of diesel fuel (No. 2D) and their calorific value is lower. Therefore it is not possible to obtain more benefit. Coating combustion chamber parts with a ceramic material seems an effective solution for improving performance of these lower-quality fuels compared with No. 2D and also exhaust emission values. Since it allows to use higher combustion temperatures. In the present study, surfaces of cylinder head, piston. exhaust and inlet valve of a four-stroke, direct injection, single cylinder diesel engine were coated with molybdenum (Mo) by plasma spray method. Thus, thermal barrier characteristic was brought to these parts. Variances in performance and emission values of cotton methyl ester and 2D fuel mixtures were studied in the ceramic coated and uncoated engines under the same running conditions. Performance (up to 2.2-2.3% for engine power, up to 3.5-5.6% for specific fuel consumption) and emission values (up to 17-22% for CO, up to 5.2-10% for smoke) of the test fuels were improved in the coated engine compared with the uncoated engine. However, because the coated engine ran at higher temperatures compared with the uncoated engine, an increase (up to 6.5-7.4%) was seen in NO(x) emission in cases of all test fuels. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Thermal barrier coating; Methyl ester; Exhaust emissions